Effects of different treatments on seed dormancy breaking and germination in Acer cappadocicum Gleditsch var. cappadocicum : Utjecaj različitih tretmana na prekid dormantnosti i klijavost sjemena Acer cappadocicum Gleditsch var. cappadocicum - Erdogan Genç, Hanife (Array, 2020)
This study was carried out to determine effects of different pretreatment on seed germination and to overcome dormancy in Acer cappadocicum seeds. The seeds were collected in 2008 three times with aproximately 15-days intervals. In order to overcome dormancy, several germination treatments were applied. The treatments were (1) different seed collection time, (2)soaking in water, (3) cold-moist stratification and (4) GA3 (gibberellic acid) application. The treated seeds were germinated in growing chamber at 5 0C and in greenhouse conditions. This research showed that seeds of Acer cappadocicum exhibit physiological dormancy and require stratification period to overcome seed dormancy. The highest germination percentage in the growing chamber subjected to GA3 process after eight weeks of stratification treatment was 62 % for Acer cappadocicum seeds. The highest germination percentage in greenhouse was obtained with cold stratification after eight weeks (95 %). It was found out that GA3 treatment had a significant effect on germination in growth chamber + 5 0C but GA3 treatment didn’t have a significant effect on germination in greenhouse conditions. GA3 treatment and soaking of unstratified seeds in water for 48 hr didn’t have any positive effect on germination value in greenhouse conditions. Although growth chamber and green house results both indicated that seed collection time did not seem to play a role as statistically on seed germination, Duncan’s test showed that the third seed collection time was in a different group.